Dual conjugation of magnetic nanoparticles with antibodies and siRNA for cell-specific gene silencing in vascular cells - Karpinska, Katarzyna; Li, Lin; Wang, Tao (Frontiers in Drug Delivery, 2024)
RNA therapy is a rapid expending field and brings great promise to achieve targeted gene silencing and contribute to personalised medicine. However, the delivery of the RNA molecules specifically into targeted organ or cells are still challenging. To overcome the hurdle a number of nanocarriers have been developed with pros and cons. This study was designed to develop a simple and cost-effective approach to functionalise the biodegradable magnetic iron nanoparticles (MNPs) for cell-specific siRNA delivery. MNPs were synthesised based on a co-precipitation method and further functionalised with sodium citrate and polyethyleneimine (PEI) followed by material characterisation using TEM, FTIR and Zeta potential. The citrate and PEI coated MNPs were further conjugated with CD31 antibody and complexed with siRNA and using a linker-free approach. The siRNAs loaded MNPs successfully knocked down the expression of GAPDH in human endothelial cells (ECs) and NOTCH3 in human vascular smooth muscle cells (VSMCs). In a ECs and VSMCs co-culture system under shear stress to mimic blood flow, the siRNA and CD31 conjugated MNPs specifically targeted and delivered siRNA into the ECs. Our approach represents a versatile platform that could be adopted for targeted siRNA delivery in general.